Utilization of learning management system portal: perspective from higher education students - Mohd Ayub, Ahmad Fauzi; Ahmad Tarmizi, Rohani; Wan Jaafar, Wan Marzuki; Wan Ali, Wan Zah; Wong, Su Luan (WSEAS Press, 2010)
This study aimed to identify the utilization of Calculus Learning Portal Learning (CALePORT) in teaching and learning of Calculus at the University. We examined four factors viz-a-viz the students’ technology competencies, the role of lecturers, access to CALePORT and attitude towards the usage of CALePORT. Findings showed that the highest mean refers to students’ technology competencies (M = 3.27) followed by attitudes toward the usage of CALePORT (M = 2.51), the role of lecturers (M = 2.44) and access to the portal (M =2.36). Research findings also showed that there was a strong relationship between lecturers role [r (214) = 0468; p <.01] and access to CALePORT [r (214 )= 0327; p<.01] with the attitudes toward using CALePORT. However there is no relationship between students’ technology competencies with attitudes toward using the learning portal.